Strengthening capacity for species conservation in South-east Asia: a provisional assessment of needs and opportunities for the Asian Species Action Partnership. Issue 5 (9th September 2022) - Chao, Nerissa; Loffeld, Thirza A. C.; Mastro, Kate; Willcox, Daniel H. A.; Guthrie, Vicki; Rao, Madhu
Abstract: South-east Asia is home to exceptional biodiversity, but threats to vertebrate species are disproportionately high in this region. The IUCN Species Survival Commission Asian Species Action Partnership aims to avert species extinctions. Strengthening individual and organizational capacity is key to achieving long-term, sustainable conservation impact, and is a core strategic intervention for the Partnership. To look at the needs and opportunities for developing capacity for species conservation in South-east Asia, we undertook a needs assessment with organizations implementing species conservation within this region. We conducted a review of available training opportunities, mapping them against a list of identified competences needed for species conservation to determine gaps in current training. Our assessments revealed an imbalance in the focus of training opportunities vs the actual competences needed for effective species conservation, and that training opportunities within South-east Asia are limited in number and highly competitive. These findings corroborate other similar reviews, particularly on capacity gaps in the Global South. We discuss the implications of our review and use the findings to generate recommendations.